Muslims in Maine: Eid Mubarak! - Jalali, Reza (Maine Policy Review, 2015)
In spite of the fact that Maine is one of the whitest and least diverse states in the country, the state is also home to vibrant Muslim communities. Reza Jalali presents a look at various aspects of Muslim life in Maine, from celebrations of a religious festival to the history of Muslims and their religious and community organizations in the state.